PENTINGNYA KETERAMPILAN DASAR MENGAJAR BAGI MAHASISWAPRAKTEK PENGALAMAN LAPANGAN (PPL) PRODI PENDIDIKANMATEMATIKA - Yuni Rhamayanti (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2018)
The idea of this article aims to explain the perception of the importance of teaching skills of PPL students of Mathematics Education Program UGN Padangsidimpuan. This conceptual article is based on observations to one of the schools where the Student conducts the Field Experience Practice (PPL), an interview with one of the teachers, and a literature study on the study of basic skills concepts in teaching mathematics at junior and senior high schools. Based on the discussion of the contents of this article it is concluded that the skills of teaching students PPL Mathematics Education UGN Padangsidimpuan can be said has been applied if most of these skills can be implemented well by students of PPL, ranging from opening and closing lessons to teaching small groups and individuals. So the authors are advised as a material consideration in the future, namely to students who want to implement PPL should improve the ability to understand basic skills of teaching. Students should prepare themselves physically, psychologically and materially so as not to have difficulty while teaching in front of the class and get used to interact well, Lecturers of Mathematics Education should enrich the knowledge of students in understanding basic mathematics or more related to junior high and high school materials , and to the pamong teachers should provide an objective value to the students in accordance with that implemented by PPL students.Keywords: Field Experience Practice, Mathematics Education, teaching skills